PENGARUH KETERSEDIAAN FASILITAS UMUM TERHADAP HARGA JUAL PERUMAHAN DI KAWASAN MANGUPURA - Bayuprima, I Gd Raka Natha; Sutarja, I N.; Yanse, I W. (JURNAL SPEKTRAN; Vol 4 No 2 (2016): Vol. 4, No. 2, Juli 2016, 2016)
Abstract: Mangupura region as the central government of Badung regency, the last few years has developed very fast. Increased development is a result of market demand for homes is high and land prices are relatively affordable. This study aims to determine what factors are dominant to affect the selling price of the home, assess the influence of public facilities to the selling price of the house has to offer developers, as well as assess the suitability of public facilities provided are in accordance with the selling price of the house has to offer. To get data in this study using two different methods, quantitative data (answers from the questionnaire) and qualitative data (the answers of the interview). The data were processed using a statistical test, with five score classifications, then the data is presented with the relative frequency distribution and the analysis that used is multiple linear regression analysis. The results of multiple regression analysis performed indicates that public facilities provided by the developer significantly effect on peoples satisfaction in Mangupura. The dominant factor that affect consumers in buying a home is public road facility with average level 4.159. Each factor with influence level of selling price has positive linear relationship, except on public wastewater disposal facilities (-0439), assuming the higher needs of residents for these factors, the higher the level of satisfaction of the inhabitants of the factors of public facilities in residential areas. Advice that can be given of the results of this study is on the development of a region should pay attention to public facilities to be provided should be adjusted to the standard housing legislation.
Keywords: Public facility, Residential, Housing, Mangupura Region